Barriers to successful treatment of alcohol addiction as perceived by healthcare professionals in Thailand - a Delphi study about obstacles and improvement suggestions - Kulnaree Hanpatchaiyakul; Henrik Eriksson; Jureerat Kijsomporn; Gunnel Östlund (Taylor & Francis Group, 2016)
Background: Many Thai people experiencing alcohol addiction do not seek help, and those who do often have inadequate access to treatment. There are few research studies focusing on alcohol addiction treatment in Thailand. Objective: The purpose of the current study was to identify barriers to the treatment of alcohol addiction and to collect experts' suggestions for improving treatment in Thailand. The Delphi technique was used to achieve consensual agreement among an expert panel within the field of alcohol addiction and treatment. Design: Three rounds of a Delphi survey were completed by a panel of experts in alcohol addiction, including physicians, nurses, social workers, psychologists, healthcare officers, and an Alcoholics Anonymous member. The open-ended answers provided by 34 experts in the first round resulted in 60 statements, which were later grouped into three themes. After three rounds of questionnaires, 51 statements were accepted as consensus. Results: Thirty-two experts participated in all three Delphi rounds. Over 80% of participants were particularly concerned about five obstacles to alcohol addiction treatment. The majority of suggestions from the expert panel were related to patients' right to treatment and the national policy for reducing the negative effects of alcohol. According to the results of the present study, the experts suggested that the treatment of alcohol addiction should be continuous from primary care to tertiary care, and convenient pathways should be established in healthcare services. The experts would also like to increase the number of healthcare providers and improve their knowledge and skills in working with people experiencing alcohol addiction. Conclusions: Equal rights to health and treatment for people experiencing alcohol addiction in Thailand require policy improvements, as well as acceptance and awareness of alcohol addiction from both the public and policymakers.